Colour Assays: An Inside Look into Alentejo Traditional Limewash Paintings and Coloured Lime Mortars - Gil, M. (2012)
A series of colour assays were conducted taking into account old bibliographic recommendations and oral testimony regarding traditional lime painting technology from the Alentejo (South Portugal) region. The main objectives were: (a) the colorimetric analysis of paintings made with different limewash preparation methods; (b)the comparison between natural processed red and yellows ochre pigments (‘‘home made’’ and from industrial origin) and synthetic iron oxides in different concentrations and lime proportions; (c) the evaluation of the colorimetric CIELAB coordinates during the lime carbonation process in coloured mortars and limewashes. The results shows that the evolution of L*, a*, and b* during the carbonation process is independent of pigment concentration and paint thickness but dependent of pigment composition and finishing technique (lime painting or coloured mortar). They also emphasize the importance of surface appearance attributes and its influence on the colorimetric parameters.